Fractination and Characterization of Pandan Jeronggi Fruit (Iris Domestica (L.) Goldblatt & Mabb) Ethanol Extracts As Well As Antibacterial Activities from Each Fraction - K, Marpaung J; P, Sitorus; D, Suryanto (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: The research aims to find out antibacterial activity of ethanol extract, n-hexane fraction, ethylacetate fraction and residual fraction (water) of Pandan Jeronggi fruit against several types of bacteria. Methods: Antibacterial activity test was carried out using the agar diffusion method by measuring the diameter of the clear zone around the paper disc. Results: The results of the simplicia characterization and ethanol extract obtained water content of 9.23% and 19.13%. Phytochemical screening test results in thick extract there are alkaloids, flavonoids, glycosides, saponins, and tannins. Antibacterial activity test results shows the inhibition of gram-positive and gram-negative bacteria. Ethyl acetate fraction and ethanol extract have the highest antibacterial activity with a concentration of 500 mg/ ml inhibitory diameter of 13.68 mm for Sthaphylococcus aureus and 11.44 mm for pseudomonas aeruginosa bacteria. Ethanol extract in Sthaphylococcus aureus 12.12 mm and 10.76 mm for pseudomonas aeruginosa bacteria, while the remaining fraction shows not too high inhibitory properties such as ethanol extract and ethylacetate fraction which is 10.42 mm in Sthaphylococcus aureus and 9.24 for pseudomonas aeruginosa bacteria in the n-hexane fraction has no inhibitory power. The KKt results obtained from the ethyl acetate fraction contained three visual stains, with AlCl3 spray two are also three stains, with ammonia vapor there are three stains, the compound contained in the ethyl acetate fraction suspected as an antibacterial activity is fenolik.